"THE ALEPH LATIN AMERICAN" The simultaneity as a symptom for literary criticism in Latin America? - Amalia Franco Castaño (Corporación Universitaria Minuto de Dios, 2009)
The phenomena of literary criticims in latin America along with the dialogue other disciplines, such as the mass media role and the popular discourses, have provoked firts, a line of work whit resilient proposal towards the totalization, radicalism and monological responses, where the literature situation is shown as an objet of culture comprehension. And second, the cultural context as a principle for the aesthetics understanding hang this in mind. The purpose of this article is to digin on how those phenomen of cultural criticism in Latin America, have been oriented, in the last decade, and how their different and eclectic proposals offer a vission of what national and national literature, are in a time in which globalization, simultaneity and hybridation still being the reference for literature discourses.